SPECIAL SMARANDACHE CURVES IN R13 - Gurses, Nurten (Bayrak); Bektas, Ozcan; Yuce, Salim (ANKARA UNIV, FAC SCI, 2016)
In this study, we determine TN-Smarandache curves whose position vector is composed by Frenet frame vectors of another regular curve in Minkowski 3-space R-1(3.) Then, we present some characterisations of Smarandache curves and calculate Frenet invariants of these curves. Moreover, we classify TN, TB, NB and TNB-Smarandache curves of a regular curve parametrized by arc length alpha by presenting a brief table with respect to the causal character of alpha. Also, we will give some examples related to results.
Keywords: Minkowski space; Frenet invariants; Smarandache curves; Mathematics